2016
DOI: 10.1080/17435390.2016.1206149
|View full text |Cite
|
Sign up to set email alerts
|

Interactions of CuO nanoparticles with the algae Chlorella pyrenoidosa: adhesion, uptake, and toxicity

Abstract: The potential adverse effects of CuO nanoparticles (NPs) have increasingly attracted attention. Combining electron microscopic and toxicological investigations, we determined the adhesion, uptake, and toxicity of CuO NPs to eukaryotic alga Chlorella pyrenoidosa. CuO NPs were toxic to C. pyrenoidosa, with a 72 h EC50 of 45.7 mg/L. Scanning electron microscopy showed that CuO NPs were attached onto the surface of the algal cells and interacted with extracellular polymeric substances (EPS) excreted by the organis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
68
0
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 136 publications
(73 citation statements)
references
References 41 publications
3
68
0
2
Order By: Relevance
“…In this study, the heteroagglomeration between the precipitation of Th(OH) 4 and algae cells could possibly lead to a reduction in the light available to cells and thus decrease the chlorophyll contents. On the other hand, it might be a mechanism of egodefence that the exposed cells aggregated together to decrease the physical contact with Th, as reported by Zhao et al [21], who showed that the aggregated algae cells act as a barrier to prevent the direct damage of CuO NPs to the cell wall and membrane.…”
Section: Resultsmentioning
confidence: 91%
See 1 more Smart Citation
“…In this study, the heteroagglomeration between the precipitation of Th(OH) 4 and algae cells could possibly lead to a reduction in the light available to cells and thus decrease the chlorophyll contents. On the other hand, it might be a mechanism of egodefence that the exposed cells aggregated together to decrease the physical contact with Th, as reported by Zhao et al [21], who showed that the aggregated algae cells act as a barrier to prevent the direct damage of CuO NPs to the cell wall and membrane.…”
Section: Resultsmentioning
confidence: 91%
“…The TEM images show that nano-sized Th(OH) 4 was deposited both inside and outside the cells. Recent progresses in the aquatic toxicity of engineered nanomaterials suggest that insoluble nano-sized particles might exhibit toxicity to green algae by the following processes: (1) the shading effect may attenuate the photosynthesis by reducing light transmittance; (2) the heteroagglomeration and physical interaction may lead to the internalization of nanoparticles, cell membrane disruption and endocyte outflow; (3) the permeation and entry of nanoparticles into the cells may induce the elevation of intracellular ROS levels and the membrane lipid peroxidation [19,20,21,24,25,26]. All these processes might contribute to the toxic effects of Th to C. pyrenoidosa .…”
Section: Resultsmentioning
confidence: 99%
“…In this study, the heteroagglomeration between the precipitation of Th(OH)4 and algae cells could possibly lead to a reduction in the light available to cells and thus decreasing the chlorophyll contents. On the other hand, it might be a mechanism of egodefence that the exposed cells aggregated together to decrease the physical contact with Th, as reported by Zhao et al [26] that the aggregated algae cells acting as a barrier to prevent the direct damage of CuO NPs to the cell wall and membrane . Figure 5G and I are higher magnification of the areas marked by the black boxes in Figure 5H.…”
Section: Chemical Species Of Th In the Mediamentioning
confidence: 97%
“…The TEM images show that nano-sized Th(OH)4 was deposited both inside and outside the cells. Recent progresses in the aquatic toxicity of engineered nanomaterials suggest that insoluble nano-sized particles might exhibit toxicity to green algae by the following processes: (1) the shading effect may attenuate the photosynthesis by reducing light transmittance; (2) the heteroagglomeration and physical interaction may lead to the internalization of nanoparticles, cell membrane disruption and endocyte outflow; (3) the permeation and entry of nanoparticles into the cells may induce the elevation of intracellular ROS levels and the membrane lipid peroxidation [24][25][26][29][30][31]. All these processes might contribute to the toxic effects of Th to C. pyrenoidosa.…”
Section: Ultrastructural Alterationsmentioning
confidence: 99%
“…Graphene -a two-dimensional single-atom-thick nanomaterial with unique structural, mechanical and electronic properties has potential biomedical applications [52][53][54]. Its high specific surface area allows high-density biofunctionalization for nanotechnology-based drug delivery [55][56][57]. Furthermore, its smooth, contiguous topography and bio-persistence play a unique role in foreign-body-induced carcinogenesis and tumor progression [58,59].…”
Section: Interaction Of Polymers and Nanoparticles With Membranesmentioning
confidence: 99%